Cancellation: A Reality in Liquid Modernity - Escobar-Peralta, Mariana; Gómez, Andrés-Felipe; ´Puliche, Natalia-Andrea (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This document is an in-depth analysis of cancellation on the internet, a phenomenon that has become increasingly common on social networks. The text explores how the massiveness of information, digital freedom of expression and cyberbullying influence this phenomenon, as well as how modernity and liquid generation have changed our perception of religion, morality and sorority. In addition, the importance of being critical and careful when consuming information and evaluating the source of it is discussed. It highlights the importance of communicative responsibility and the significant impact that actions can have on others. Considering the topic discussed in the document, it is based on several theoretical frameworks to analyze the phenomenon of cancellation on the internet and its implications in society. One of the main theoretical frameworks is the liquid modernity theory of Zygmunt Bauman, which is used to understand how the cancellation culture manifests on the internet and social networks. Liquid modernity is characterized by a lack of solid and stable structures, while the culture of cancellation is based on the idea that anyone can be canceled at any time, regardless of their social position or reputation. Likewise, ethics and philosophy are important concepts to analyze the importance of communicative responsibility and freedom of digital expression. Reference is made to the book "Ethics for Amador" by Fernando Savater, which is used to reflect on the importance of ethics in online actions and expressions. The importance of digital freedom of expression is discussed and how it can be protected without compromising communicative responsibility. Finally, it includes testimonies of people who have found strength and healing through their faith in God and how this can help overcome eating disorders.